Building the modern workplace with SharePoint Online : solutions with SPFx, Power Automate, Power Apps, Teams, and PVA - V. P, Harinarayanan (Apress, 2021)
Build a digital workplace solution from scratch using SharePoint Online, Teams, and the Power Platform. The book will help you implement all the modern capabilities of the SharePoint Framework, Teams, and Power Platform into a SharePoint Online solution. You will begin your journey with a short overview of the basics of SharePoint Online. You will then work through a case study with a solutions approach to implement various business requirements using SharePoint Online. Further, you will learn how to provision sites using PnP and build SharePoint forms using out-of-the-box forms. The next section covers Power Apps and Power Automate, followed by a discussion on SharePoint Framework where you will learn to customize SharePoint Online sites using SPFx. Moving forward you will go through configuration and customization of PnP modern search. Wrapping up, you will integrate Microsoft Teams, MS Graph, and Power Virtual Agents with SharePoint Online. After reading Building the Modern Workplace with SharePoint Online you will be able to build SharePoint Online sites according to your business requirements and integrate SharePoint Online with other services for a modern workplace experience. You will: Build modern workplace solutions using SharePoint Online out-of-the-box features Use Power App forms, SPFx web parts, SPFx extensions, and modern search Create Power Automate workflows Develop Teams solutions and chatbots Use Microsoft Graph and PnP JS with SharePoint Customize search capabilities.